Critical parameters for robust Agrobacterium‐mediated transient transformation and quantitative promoter assays in Catharanthus roseus seedlings - Lauren F. Cole‐Osborn; Emma Meehan; Carolyn W. T. Lee‐Parsons (Plant Direct)
Abstract Agrobacterium‐mediated transient expression methods are widely used to study gene function in both model and non‐model plants. Using a dual‐luciferase assay, we quantified the effect of Agrobacterium‐infiltration parameters on the transient transformation efficiency of Catharanthus roseus seedlings. We showed that transformation efficiency is highly sensitive to seedling developmental state and a pre‐ and post‐infiltration dark incubation and is less sensitive to the Agrobacterium growth stage. For example, 5 versus 6 days of germination in the dark increased seedling transformation efficiency by seven‐ to eight‐fold while a dark incubation pre‐ and post‐infiltration increased transformation efficiency by five‐ to 13‐fold. Agrobacterium in exponential compared with stationary phase increased transformation efficiency by two‐fold. Finally, we quantified the variation in our Agrobacterium‐infiltration method in replicate infiltrations and experiments. Within a given experiment, significant differences of up to 2.6‐fold in raw firefly luciferase (FLUC) and raw Renilla luciferase (RLUC) luminescence occurred in replicate infiltrations. These differences were significantly reduced when FLUC was normalized to RLUC values, highlighting the utility of including a reference reporter to minimize false positives. Including a second experimental replicate further reduced the potential for false positives. This optimization and quantitative validation of Agrobacterium infiltration in C. roseus seedlings will facilitate the study of this important medicinal plant and will expand the application of Agrobacterium‐mediated transformation methods in other plant species.